THE EFFECTIVENESS OF E-LEARNING APPLICATION BASED ON FRAMEWORK CODEIGNITER IN THE COVID19 PANDEMIC PERIOD (CASE STUDY STAIN TEUNGKU DIRUNDENG MEULABOH) - Mukhlizar Mukhlizar; Hijrah Hijrah; Herman Herman (UIN Ar-Raniry, 2020)
The rapid development of the covid-19 virus requires learning and teaching to be carried out online or remotely, the online learning process is carried out to break the chain of spreading the covid-19 virus. In the application of online learning STAIN Tengku Dirundeng Meulaboh uses an e-learning application developed with a codeigniter framework. The use of the existing MVC method in the Codeigniter framework can facilitate the development of e-learning applications that must adapt to user needs, therefore a study was conducted to determine the effectiveness of STAIN Tengku Dirundeng Meulaboh e-learning users during the Covid-19 pandemic. Measuring the effectiveness of this is done through a questionnaire by asking several questions to measure user satisfaction based on the End User Computing Satisfaction (EUCS) method. Based on the research results, it was found that 94% of e-learning users were greatly helped in the learning process and the level of user satisfaction was 85%.